Combined Papillated Bowen Disease and Clear Cell Atypical Fibroxanthoma - Dimas Suárez-Vilela; Francisco Izquierdo-García; Francisco Domínguez-Iglesias; Jose Ramón Méndez-Álvarez (Karger Publishers, 2010)
We describe a case of papillated Bowen disease (PBD), associated with a clear cell atypical fibroxanthoma (CCAFXA). The epidermal lesion showed a bowenoid papillomatous growth pattern with histologic features suggestive of infection by human papilloma virus (HPV). In the dermis a neoplasm made up by spindled or polygonal cells with wide clear cytoplasm and moderate nuclear pleomorphism was found. Immunohistochemical characteristics of these two lesions were clearly different. The atypical cells of the intraepidermal proliferation were positive for AE1-AE3 anticytokeratin antibody, EMA, p16, p53 and p63. The dermal tumor was positive for vimentin, CD10, CD68, CD99, alpha-1-antitrypsin and c-kit. Histological features and immunohistochemical profile of the dermal tumor corresponded to a CCAFXA, a very uncommon neoplasm of which only 10 cases have been reported. In situ hybridization for numerous types of HPVs was negative in both lesions.